Modernization as the Basis for Democracy in Indonesia - Khosiin, Khamam; Fikri Al Farabi; Zainuddin Fanani (International Journal of Educational Research Excellence (IJERE), 2023)
The role of Islamic modernization as the basis of democracy in Indonesia. Against the backdrop of sensitive ethnic, linguistic, religious and geographic diversity, this country requires a wise approach to maintain unity and integrity. The author links democracy with the modernization of Islam, discusses the history of democracy in Islam, especially during the time of the Prophet Muhammad SAW, and links it to the concept of the caliphate. In the context of Indonesian democracy, research highlights restrictions on government action, tolerance, equality before the law, free elections, freedom of political parties, respect for people's rights, and respect for minority rights. This research criticizes the view that democracy only succeeds after an era of authoritarianism, while trying to raise public awareness about their role in maintaining democracy. The research discusses the risks of political Islamization in the democratic party in Indonesia. This is highlighted as a challenge to the modernization of Islam, where Islamic political parties are often misunderstood as sources of radicalism. However, research emphasizes that the modernization of Islam as a pillar of democracy must be directed at tolerance, social justice, and a positive relationship between Islamic religion and politics, without ignoring the risk of political Islamization which could damage democracy. This research concludes that Indonesia needs a democratic approach based on Islamic modernization to achieve unity, tolerance and social justice. However, it is necessary to avoid the politicization of Islam which has the potential to damage stability and democracy.